Atom Probe Tomographic Characterization of Nanoscale Cu-Rich Precipitates in 17-4 Precipitate Hardened Stainless Steel Tempered at Different Temperatures. (16th March 2017) - Wang, Zemin; Fang, Xulei; Li, Hui; Liu, Wenqing
Abstract: The formation of copper-rich precipitates of 17-4 precipitate hardened stainless steel has been investigated, after tempering at 350–570°C for 4 h, by atom probe tomography (APT). The results reveal that the clusters, enriched only with Cu, were observed after tempering at 420°C. Segregation of Ni, Mn to the Cu-rich clusters took place at 450°C, contributing to the increased hardening. After tempering at 510°C, Ni and Mn were rejected from Cu-rich precipitates and accumulated at the precipitate/matrix interfaces. Al and Si were present and uniformly distributed in the precipitates that were <1.5 nm in radius, but Ni, Mn, Al, and Si were enriched at the interfaces of larger precipitates/matrix. The proxigram profiles of the Cu-rich precipitates formed at 570°C indicated that Ni, Mn, Al, and Si segregated to the precipitate/matrix interfaces to form a Ni(Fe, Mn, Si, Al) shell, which significantly reduced the interfacial energy as the precipitates grew into an elongated shape. In addition, the number density of Cu-rich precipitates was increased with the temperature elevated from 350 up to 450°C and subsequently decreased at higher temperatures. Also, the composition of the matrix and the precipitates were measured and found to vary with temperature.